XRF data sheet: overbank silt-clay deposition sampling (4*4 km grid, Weiße Elster catchment, Salsitz-Trebnitz section) - Helen Ballasus; Christoph Zielhofer; Birgit Schneider; Hans von Suchodoletz (PANGAEA, 2021)
We used stationary XRF spectrometry for analysing elemental composition of bank and streambed samples from Weiße Elster sub-basins (refined grids of 4*4 km). For XRF sample preparation freeze-dried catchment sediments (8 g) were seaved (2mm) to discard the gravel fraction and large organic matter. Further homogenization was undertaken by grinding the samples with a vibratory Retsch mill MM 200. We created uniform pellets by pressing the powdered samples with a carbon-based binding agent in a Vaneox press at 20 t for 2 min. We conducted elemental analyses in a He atmosphere using a Spectro Xepos energy dispersive XRF spectrometer. The XRF element data of the refined 4*4 km sampling grid of recent fluvial sediments in the direct proximity to the Salsitz transect are provided here. The data set has to be understood as a supplement or densification of the 8*8 km sampling grid of the Weiße Elster river catchment: doi:10.1594/PANGAEA.937926.